Answer:
D: humor.
Step-by-step explanation:
it's just common sense. I am not a gen z so I should know.
Answer:
It's is A and D.
Step-by-step explanation:
Tan^2 theta cos 2theta
= (sin^2 theta / cos^2 theta )( 2 cos^2 theta - 1)
= 2 sin^2 theta - sin^2 theta / cos^2 theta
= 2 sin^2 theta - tan^2 theta.
Tan^2 theta cos 2theta
= ( 1 / cot^2 theta) * cos 2theta
= cos 2theta / cot^2 theta.
Step-by-step explanation:
-7 because i now this by myself aND blah blah blah blah blah blah blah blah blah blah blah blah blah blah step by step nice
nice nice
No
They are not equivalent.